Association of Hyperprolactinemia in Females with Infertility - Saba, Nasim; Rashid, Sobia; Ayub, Hina; Inam Khan, Rakhshinda (Indus Journal of Bioscience Research, 2025)
Introduction: Hyperprolactinemia is one of the most frequent endocrinological disorders in women that affects the hypothalamic-pituitary gonadal axis, resulting in infertility. It plays a crucial role in reproductive disorder outcomes aligned with hormonal irregularity, PCOS, and thyroid disorders. Objectives: Consequently, to explore the correlation between hyperprolactinemia and female infertility with a focus on hormonal and metabolic changes, as well as on comorbidities like PCOS and hypothyroidism. Materials and Methods: The present study was a cross-sectional study carried out Department of Gynaecology and Obstetrics, District Headquarter Teaching Hospital/ Gomal Medical College, Dera Ismail Khan, Pakistan in the duration from January, 2024 to June, 2024. One hundred fifty infertile women aged 18–40 across the general outpatient clinic were recruited, and 78 had hyperprolactinemia. Clinical and hormonal data samples were taken and processed using the Statistical Package for Social Sciences (SPSS). Results: Hyperprolactinemia was meaningfully correlated with menstrual abnormalities, PCOS, and hypothyroid problems. Infertile women in their study had significantly increased prolactin levels, which resulted in lower levels of LH, FSH, and estradiol and higher levels of BMI, as well as insulin resistance. Conclusion: Hyperprolactinemia causes hormonal and metabolic alteration and affects female fertility. Hearing and treatment at an early stage of fertility problems and comprehensive therapeutic intervention may enhance fertility.